High Root Biomass and Variation in Root Functional Traits Allow Non‐Native Grass Species to Invade Tropical Open Savannahs in Brazil - Le Stradic, Soizig [UNESP]; Damasceno, Gabriella [UNESP]; Cancian, Leonardo Farage; Donadieu, Maéva; Kollmann, Johannes; Fidelis, Alessandra [UNESP] (Wiley, 2025)
ABSTRACT Aims Root traits are critical for resource acquisition, particularly in nutrient‐limited environments such as open savannahs, and any changes in these traits can impact ecological processes. However, it is poorly understood whether invasive species outcompete natives by competitive superiority in nutrient acquisition (‘exploitation competition’) or by interfering with natives by space occupancy (‘interference competition’). Location Cerrado, south‐eastern Brazil. Methods We selected five sites of open savannahs, each consisting of two paired subsites, that is, non‐invaded or invaded by Urochloa grass species. We assessed community‐level root biomass and depth distribution in the upper 1 m of soil. We measured root biomass and functional traits for fine roots (< 2 mm) classified as absorptive and transport roots in the uppermost soil layers (0–30 cm). Results Invaded and non‐invaded plant communities differed primarily in root trait and biomass in the upper soil layer (0–10 cm). Invaded communities showed higher root biomass and root length density (RLD) compared to non‐invaded communities, evidencing space occupancy through a larger root system. Species in invaded communities had roots with larger diameters, but lower root tissue density (RTD) and lower root dry mass content (RDMC), commonly associated with fast root spreading and expansion, compared to species in non‐invaded communities. Contrarily, non‐invaded communities presented a higher proportion of absorptive roots. Conclusions Functional dissimilarities in traits related to space occupancy indicate that interference competition plays a bigger role than exploitation competition in the invasion of Cerrado by Urochloa species. Invaded savannahs are characterized by root traits and biomass allowing effective neighbor suppression. As changes in root traits such as RTD can cause modifications in ecosystem functioning, our results suggest that invasive species may modify ecosystem processes that hamper the restoration of invaded savannahs.